2021
DOI: 10.1038/s41598-021-97536-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storms on the emission of pollutants from sewage into waters

Abstract: During heavy precipitation, chemical and biological pollutants from urban and agricultural areas enter the waters from storm overflows as a result of infiltration and inflow, as well as via uncontrolled outflows from water treatment plants. Infiltration and inflow of rainwater into sewers is an especially popular and major worldwide problem. Climate forecasts indicate changes in climatic conditions towards an increase in the intensity and frequency of torrential rainfalls. It may therefore be assumed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Despite the lack of synchronisation between influent and effluent samples due to the time of treatment in the wastewater treatment plant (the wastewater entering the system as influent comes out as effluent after 18–24 h), the H9c2(2-1) cell-based SRB assay was effective to discriminate influent and effluent toxic characteristics, as a significant difference was obtained by testing the two EC 50,24h data sets ( P < 0.01), with effluents being 83.1% (mean value) less toxic to H9c2(2-1) cells than influents, thus demonstrating the success of this assay to evaluate the toxicity reduction of the wastewater treatment process. In December 7th, toxicity testing showed that the effluent (EC 50,24h = 813%) was more toxic than the influent (EC 50,24h = 1668%) (Table 1 ), which was possibly due to precipitation since it rained the night and the days before (data not shown), and it is known that rainwater can enter the municipal wastewater collection system and impair the performance of treatment facilities (Hummel et al, 2018 ), therefore impacting wastewater quality parameters (Suchowska-Kisielewicz & Nowogoński, 2021 ). In fact, five of the parameters evaluated—NO 3 − , Fe, Cr, Mn and Ni—showed higher values in the effluent than in the influent collected on that date (Tables S 1 and S 2 , supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of synchronisation between influent and effluent samples due to the time of treatment in the wastewater treatment plant (the wastewater entering the system as influent comes out as effluent after 18–24 h), the H9c2(2-1) cell-based SRB assay was effective to discriminate influent and effluent toxic characteristics, as a significant difference was obtained by testing the two EC 50,24h data sets ( P < 0.01), with effluents being 83.1% (mean value) less toxic to H9c2(2-1) cells than influents, thus demonstrating the success of this assay to evaluate the toxicity reduction of the wastewater treatment process. In December 7th, toxicity testing showed that the effluent (EC 50,24h = 813%) was more toxic than the influent (EC 50,24h = 1668%) (Table 1 ), which was possibly due to precipitation since it rained the night and the days before (data not shown), and it is known that rainwater can enter the municipal wastewater collection system and impair the performance of treatment facilities (Hummel et al, 2018 ), therefore impacting wastewater quality parameters (Suchowska-Kisielewicz & Nowogoński, 2021 ). In fact, five of the parameters evaluated—NO 3 − , Fe, Cr, Mn and Ni—showed higher values in the effluent than in the influent collected on that date (Tables S 1 and S 2 , supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…In aquatic species, they reduce the number of living organisms, causing biological alterations due to the nonmetabolization of metals. Wastewater contamination in aquifers produces a high concentration of biochemical oxygen demand (BOD), ammonia and hydrogen sulfide (Suchowska-Kisielewicz & Nowogoński, 2021). Most countries in the world have contamination of wastewater by fecal viruses, added to that; it is accompanied by endocrine descriptors, pharmaceutical products and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, water infrastructure has already been struggling to keep pace with changes to rainfall and a growing population (Rouse, 2014;Suchowska-Kisielewicz & Nowogo nski, 2021). The global water monitoring program reported one-third of all rivers in Africa, Asia, and Latin America severely affected by pathogen pollution (UNEP, 2016).…”
mentioning
confidence: 99%